MEPCP: an effective game-based learning for Mandarin endocentric phrases / Mok Soon Sim, Lau Suk Khin, and S. Suchithra K. Sankaran - Mok, Soon Sim; Lau, Suk Khin; K. Sankaran, S. Suchithra (Universiti Teknologi MARA Cawangan Kedah, 2023)
This study is to investigate the effectiveness of using Mandarin Endocentric Phrases Crossword Puzzle (MEPCP), an online game-based teaching tool, to teach Mandarin Endocentric Phrases (MEP) in Mandarin classrooms. Game-based learning is widely acknowledged as an effective method to increase engagement among learners in foreign language classrooms. Within this backdrop, MEPCP was created to enable learners to experience the structuring of correct MEP in an engaging way. This study explores the efficacy of MEPCP in achieving the mastery of MEP. 155 students responded to 28 items on a 5-point Likert scale questionnaire. Data analysis was done using SPSS version 24. Findings reveal that the students learn MEP more effectively via MEPCP. It is also evident that MEPCP is easily accessible and user friendly. Besides being learner-centred and entertaining, results indicate that it provides immediate feedback to the students. The conclusions underline that being grounded in the constructivist paradigm, MEPCP enables learners to experience content under authentic circumstances. This suggests the implementation of MEPCP helps to improve students’ Mandarin communication skills, thus nurtures holistic individuals who can realize the aspirations of the Malaysian education system.